2019
DOI: 10.1186/s13756-019-0484-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of antibiotic pressure on multi-drug resistant Klebsiella pneumoniae colonisation in critically ill patients

Abstract: Background The aim of this study is to evaluate the risk factors for colonisation by multidrug resistant (MDR) K. pneumoniae in a critical care unit and the relationship between colonisation and the antibiotic pressure exerted by the antimicrobial treatments received by patients. Methods A prospective observational was designed. Patients admitted for more than 48 h to an intensive care unit were included. Samples for surveillance cultures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Most of the patients with CRKP infection in this study had an advanced age, long hospital stays, a history of antibiotic treatment and invasive operations or treatments during hospitalization, which have been confirmed as important risk factors for CRKP colonization. 29 , 30 It was reported that CRKP colonization can increase the risk of subsequent infection. 31 Also, the relatively weak immune function of ICU patients may enhance the invasive ability of pathogens, which can be seen in three patients with bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients with CRKP infection in this study had an advanced age, long hospital stays, a history of antibiotic treatment and invasive operations or treatments during hospitalization, which have been confirmed as important risk factors for CRKP colonization. 29 , 30 It was reported that CRKP colonization can increase the risk of subsequent infection. 31 Also, the relatively weak immune function of ICU patients may enhance the invasive ability of pathogens, which can be seen in three patients with bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%
“…Colonisation was found to be a large reservoir for AMR, with the majority of E. coli and more than half of the K. pneumoniae isolated from stool samples, as has been documented previously in Vietnamese hospitals (57) . High community usage of antibiotics in Vietnam is likely to promote colonisation with AMR bacteria, as prior treatment with antibiotics is known to lead to colonisation (58) . Colonisation itself has been identified as a risk factor for subsequent infection (59-61) , and has been previously documented in ICU patients in southern Vietnam (62) .…”
Section: Discussionmentioning
confidence: 99%
“…By removing the normal bacterial microflora, antibiotics actually provide an opportunistic niche for the emergence of antibiotic-resistant bacterial strains which no longer have to compete with the normal bacterial populations present in the body [71,72]. Klebsiella pneumoniae is a Gram negative, facultative anaerobic commensal microorganism that can cause chronic urinary tract and soft tissue infections, pneumonia, and sepsis, and mostly occurs in immunocompromised patients [73]. Klebsiella pneumoniae normally colonises the mouth, skin, and intestines.…”
Section: Commercial Development Of Antibioticsmentioning
confidence: 99%